2008
DOI: 10.1093/toxsci/kfn113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Immune System in Rats and Mice Administered Linear Ammonium Perfluorooctanoate

Abstract: Repeated high doses of ammonium perfluorooctanoate (APFO) have been reported to affect immune system function in mice. To examine dose-response characteristics in both rats and mice, male CD rats and CD-1 mice were dosed by oral gavage with 0.3-30 mg/kg/day of linear APFO for 29 days. Anti-sheep red blood cell (SRBC) IgM levels, clinical signs, body weights, selected hematology, and lipid parameters, liver weights, spleen, and thymus weights and cell number, selected histopathology, and serum corticosterone co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 29 publications
4
52
0
Order By: Relevance
“…Relative spleen and thymus weights were reduced in our WT controls exposed to 30 mg PFOA/kg (spleen) or 7.5 mg PFOA/kg (thymus). The reduction in spleen weight (Figure 2a) was consistent with our previous study (DeWitt et al, 2008) and studies by others (Yang et al, 2002a;Loveless et al, 2008) that demonstrated reductions in spleen weights in C57BL/6 mice given 30 mg PFOA/kg. However, the reduction in the relative thymus weight (Figure 2b) associated Figure 2.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Relative spleen and thymus weights were reduced in our WT controls exposed to 30 mg PFOA/kg (spleen) or 7.5 mg PFOA/kg (thymus). The reduction in spleen weight (Figure 2a) was consistent with our previous study (DeWitt et al, 2008) and studies by others (Yang et al, 2002a;Loveless et al, 2008) that demonstrated reductions in spleen weights in C57BL/6 mice given 30 mg PFOA/kg. However, the reduction in the relative thymus weight (Figure 2b) associated Figure 2.…”
Section: Discussionsupporting
confidence: 92%
“…This focus was based on a set of papers by Yang et al (2000Yang et al ( , 2001Yang et al ( , 2002b) that indicated reductions in relative spleen and thymus weights and suppression of the T-cell-dependant antibody response (TDAR). Succeeding studies of PFOA and related PFAS (PFOA, PFOS, and ammonium perfluorooctanoate [APFO, a precursor compound to PFOA]) also demonstrated suppression of the TDAR (DeWitt et al, 2008;Loveless et al, 2008) and that exposure to PFOS also affected the T-cell-independent antibody response (TIAR; Peden-Adams et al, 2008). Suppression of both the TDAR and TIAR suggests that B-cells are targeted by PFAS.…”
Section: Introductionmentioning
confidence: 99%
“…Total doses received in the Dewitt et al (2008) study appear to have been about an order of magnitude higher than the total lifetime dose received by people drinking water contaminated with 1 ng/mL PFOA. There appears to be strain as well as species sensitivity to the immunotoxic effects of PFOA, with rats being considerably less sensitive than mice (Loveless et al 2008), leading some to question the relevance of these data to humans. Immunotoxicity by PFOA in rodents appears to occur both through and independent of peroxisome proliferation (Yang et al 2000).…”
Section: Immune Thyroid Liver and Kidney Function And Sex Hormonesmentioning
confidence: 99%
“…Further, in a number of immunotoxicology studies, rats and other rodent species have been used as their immune responses have been shown to be quite comparable to the human response (Esquifino et al, 1996;Minor, 2011;Loveless et al, 2008). Through the use of this particular rat model, it was hoped that the present study might provide new insights into the mechanisms responsible for the coagulopathic effects of black fly saliva in vivo and data regarding its potential efficacy for use in specific future therapeutic interventions.…”
Section: Introductionmentioning
confidence: 97%